Diversification of Farming Businesses Through the Cultivation of Neno IPB Curly Chilies at the Farmers Group Sido Makmur Talang Kelapa Banyuasin - Yursida; Karlin Agustina; Pandriadi; Evriani Mareza; M. Wahyu Firmansyah; Zulika Fatimah Wiwiti (Universitas Muhammadiyah Palembang, 2025)
Chili peppers (Capsicum annuum L.) are an important vegetable crop in Indonesia. Proliga (Double Production) technology is a technology package that doubles chili pepper production both during the on-season and off-season. This technology includes the use of superior varieties, zigzag planting distances, balanced fertilization, and routine pest and disease prevention and control. One of the superior varieties of curly chili is Neno IPB, which has obtained variety release legalization from the Indonesian Ministry of Agriculture with Decree 458./Kpts/PV.240/D/X/2023. This variety was then developed into Neno Tavi IPB, which is resistant to viruses. This chili is suitable for lowlands. Potential locations for curly chili pepper development are in Tanah Mas Indah Talang Kelapa Banyuasin through a partnership-based PKM program. The implementation methods include: 1) survey, observation and identification of partner problems, 2) licensing, partner approach and socialization, 3) training, mentoring and assistance, 4) technology application/demo plot creation, and 5) monitoring and evaluation. The results of the activities include three training sessions and the creation of demonstration plots. Currently, the chili plants have been harvested with fairly good yields. Following the PKM activities, there has been an increase in knowledge levels, as well as an increase in farmers' turnover and income.